Parler le Lubunca. Une ethnographie des pratiques langagières des travailleuses du sexe trans’ en Turquie - Gizem Bilal (Glad!)
This brief article presents some findings from research carried out since 2019 as part of a master’s degree (Bilal, 2022) and currently of doctoral research at The School for Advanced Studies in the Social Sciences (EHESS). Based on an ethnography that incorporates recordings of conversations and interviews, participant observation and field notes, I propose an introduction to Lubunca speak, emphasizing its importance for its speakers in context.